Subordination of American capital - Grundfest, Joseph A. (Journal of Financial Economics, 1990)
To economists, agency problems present challenges that can be resolved through optimal contracting or incentive mechanisms. To politicians, agency problems represent entitlements to be allocated among favored constituencies. Corporate management constitutes a powerful constituency independent of the interests of workers, local communities, and other corporate stakeholders. The political process has, for politically rational but economically dabatable reasons, systematically subordinated investors' desire to resolve agency problems to managers' desire to be protected from capital-market discipline. Politically explicit modes of analysis thus complement traditional tools of finance theory and improve our ability to explain capital-market structure and behavior.